1995
DOI: 10.1111/j.1365-3083.1995.tb03564.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Immune Responses to Native and Protein Conjugated Pneumococcal Polysaccharide Type 14

Abstract: The immune response to pneumococcal polysaccharide type 14 (PPS-14), induced by native PPS-14 was compared with the response induced by PPS-14 conjugated with CRM197 (PPS-14-CRM197). In our animal model, immunization with PPS-14-CRM197 gave a significant enhancement of anti-PPS-14 serum titres for IgM and IgG, but not for IgA. Also an increase in total number of anti-PPS-14 antibody-secreting cells was found. Using immunohistochemical techniques, a different distribution pattern of specific antibody-containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
1
5
0
Order By: Relevance
“…Our results also confirm reports that immunization with PPS conjugate vaccines can induce a strong antibody response in the absence of a spleen (3,54). The means by which conjugation of TD carriers to PPS bypasses the requirement for the spleen in the anti-PPS antibody response is currently unknown, but likely involves enhancement of the anti-PPS14 immune response in extrasplenic locations.…”
Section: Discussionsupporting
confidence: 79%
“…Our results also confirm reports that immunization with PPS conjugate vaccines can induce a strong antibody response in the absence of a spleen (3,54). The means by which conjugation of TD carriers to PPS bypasses the requirement for the spleen in the anti-PPS antibody response is currently unknown, but likely involves enhancement of the anti-PPS14 immune response in extrasplenic locations.…”
Section: Discussionsupporting
confidence: 79%
“…Asplenic or hyposplenic patients might benefit from vaccination with PCV because polysaccharide-protein conjugates can initiate an antibody response to the polysaccharide without the need for a functional spleen (19,35,37). We therefore tested the immunogenicity of PCV in splenectomized rats and showed that a series of two doses of PCV given 6 weeks after splenectomy resulted in antibody titers that were at least as high as in control rats but that the antibody response to PPS was impaired by splenectomy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This induces helper T cells to stimulate PS-specific B cells that have taken up the conjugate molecules. These B cells then produce specific antibodies and mature into memory cells (51,52).…”
Section: B Streptococcus Pneumoniaementioning
confidence: 99%